Thermodynamic equilibrium analysis of combined carbon dioxide reforming with partial oxidation of methane to syngas - Saidina Amin, Nor Aishah (2007)
The chemical equilibrium analysis on combined CH4-reforming with CO2 and O2 (combined CORM–POM) has been conducted by total Gibbs energy minimization using Lagrange's undetermined multiplier method. The equilibrium compositions of the combined CORM–POM process were considerably influenced by CH4:CO2:O2 feed ratios and operating temperatures. Methane oxidation reaction occurred predominantly at low temperatures, while the CO2 conversion was strongly influenced by the O2/CH4 feed ratio. The addition of O2 to the CORM process improved the CH4 conversion, H2 and H2O yields and also the H2/CO product ratio at the expense of CO2 conversion and CO yield. Accordingly, the optimal equilibrium conditions for the CH4:CO2:O2 ratio were within the range of 1:0.8:0.2–1:1:0.2 and a minimum requirement temperature of 1000 K.